2023
DOI: 10.1186/s12904-023-01137-0
|View full text |Cite
|
Sign up to set email alerts
|

“I can’t make all this work.” End of life care provision in natural disasters: a qualitative study

Abstract: Background Natural disasters are becoming more frequent and severe and profoundly impact the end-of-life care experience, including service provision. There is a paucity of research examining healthcare workers’ experiences in responding to care demands when disasters strike. This research aimed to fill this gap by exploring end-of-life care providers’ perceptions of the impact of natural disasters on end-of-life care. Methods Between Feb 2021-June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…However, only nine studies 26,28,35,37,44,64,65,69,70 in this theme discussed a training programme that had been implemented, highlighting that existing climate training and education for the health workforce is limited. Under planning for staff surge capacity, 4,5,8,10,14,27,28,30,31,[33][34][35][36]38,39,[41][42][43][44][45][46][47][48][49][50][53][54][55][56][57][59][60][61][62]67,70,72,[74][75][76] discussions centred on rostering considerations and contingency plans to ensure workforce surge capacity, as well...…”
Section: Responses and Preparationsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, only nine studies 26,28,35,37,44,64,65,69,70 in this theme discussed a training programme that had been implemented, highlighting that existing climate training and education for the health workforce is limited. Under planning for staff surge capacity, 4,5,8,10,14,27,28,30,31,[33][34][35][36]38,39,[41][42][43][44][45][46][47][48][49][50][53][54][55][56][57][59][60][61][62]67,70,72,[74][75][76] discussions centred on rostering considerations and contingency plans to ensure workforce surge capacity, as well...…”
Section: Responses and Preparationsmentioning
confidence: 99%
“…Thirty-nine studies reported on the impacts of climate change on the health workforce, with four main themes identified (Table 3). The most common theme in this category was the experience of system breakdown (n = 20), 4,8,10,14,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] due to unclear allocation of staff roles and remuneration, electrical outages, and inadequate processes and preparation in healthcare facilities. This was often observed alongside unsafe conditions (n = 16) studies, 10,13,28,29,37,41-51 in which the workforce was exposed to building damages, infectious diseases, and reduced T A B L E 2 Characteristics of included studies.…”
Section: Impactsmentioning
confidence: 99%
See 3 more Smart Citations